Pendapatan Asli Daerah Berdampak pada Kemandirian Keuangan Daerah - Rosmiaty Tarmizi (Universitas Bandar Lampung (UBL), 2010)
Demands for reform in all fields are supported by all Indonesian people in addressing regional issues have an impact on the financial relationship between the Central Government and Local Government. Autonomy and financial balance is fair, proportionate and transparent to be one of the demands of regional and community.The main characteristic of a region capable of autonomous autonomy lies in the financial ability to fund the implementation of local government with a degree of dependence on government is getting smaller. It is expected that the revenue (PAD) should be the biggest part in mobilizing funds local governance. Based on the above reasoning this study aims to look at local financial independence through a proportion of local revenues to total local revenue and ability to fund research activities.The method used is descriptive qualitative analysis method by analyzing the ratio to measure the level of independence local finance Bandar Lampung municipality. The results showed that the level of financial independence Bandar Lampung municipality area is still low, it is seen from the ratio of revenue to total revenue is only 8.06%, compared to operating expenses to be incurred only 9.83%, which can be financed from local revenues while the remaining comes to tax natural resources as well as transfers from the central government and the provinces. Keywords: PAD, TPD, & TBO (Pendapatan Asli Daerah, Total Pendapatan Daerah dan Total Belanja Opersional).